Teamwork in pediatric heart care - Kumar R (Wolters Kluwer Medknow Publications, 2009)
Pediatric cardiac specialties, pediatric cardiology (pediatric cardiac surgery and pediatric cardiac anesthesiology and intensive care) are only now being recognized as distinct specialties in most parts of the world. There has been a tremendous growth in knowledge in these specialties in the last 30-40 years with dramatic improvements in outcome. Pediatric cardiac care thrives on team work. The cohesiveness of the team of caregivers has a direct impact on the patient outcomes and efficiency of the system. The development of hybrid heart procedures in pediatric heart care represents an important benchmark in a team-based approach to patient care where a group of specialists with specific skills work closely together for ensuring the best possible patient outcome. Establishment of a cohesive team requires organization of group of team members with diverse skills to come together through good mutual understanding, under a leadership that actively promotes team harmony. Excellent communication among team members is a core requirement. The barriers for development and sustenance of a successful team must be recognized and overcome. They include egos of key team members as a source of conflict, time for interactions, disproportionate rewards and recognition for members of the team and traditional hierarchical arrangements. Special attention must be paid to motivating non-physician staff.